2013
DOI: 10.7547/1030361
|View full text |Cite
|
Sign up to set email alerts
|

Sever’s Injury

Abstract: The diagnosis of Sever's injury is clinical, not radiologic. Radiologic findings of increased density and fragmentation are found also in pain-free controls with high levels of physical activity and may, therefore, represent normal growth and development. We suggest that the diagnosis of Sever's injury should be based on patient history and the results of two specific clinical tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Our two previous studies have shown immediate and lasting pain relief with the heel cup, confirmed in the present study (Perhamre et al, 2010a, b). The purpose with this study was to assess the possible mechanisms behind the rapid and impressive pain relief.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our two previous studies have shown immediate and lasting pain relief with the heel cup, confirmed in the present study (Perhamre et al, 2010a, b). The purpose with this study was to assess the possible mechanisms behind the rapid and impressive pain relief.…”
Section: Discussionsupporting
confidence: 91%
“…The heel pad with its sum of cooperating compartments provides cushioning, and thereby reduces the impact force on calcaneus in heel strike (Ogden, 2000). An effective support to the heel pad therefore seems to be crucial, and this is supported by the findings in our previous study were the heel cup was shown to be superior to the wedge in giving pain relief (Perhamre et al, 2010a).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The participants were children between the ages of 8–14 years who were diagnosed with calcaneal apophysitis. The diagnosis of calcaneal apophysitis was given based on history, clinical assessment and pain elicited from placing compressive force at the medial and lateral aspects of the calcaneus [ 8 , 15 ]. Children were excluded from the study if they had a diagnosis or clinical signs of infective, reactive or rheumatoid arthritis, history of tumour or fracture of the foot or leg within the last 12 months or a Foot Posture Index-6 (FPI–6) equal to or less than −1 (supinated foot type).…”
Section: Methodsmentioning
confidence: 99%
“…The pain is often reported as worse during and post activity and may result in limping or toe walking (to avoid ground contact) on the affected limb [ 5 7 ]. Calcaneal apophysitis is diagnosed in the absence of an injury or inflammatory medical condition and with the presentation of pain on medial and lateral compression at the posterior aspect of the heel) [ 8 ]. Children may experience pain with calcaneal apophysitis for extended periods of time before seeking treatment [ 9 ] even though calcaneal apophysitis is a self-limiting condition.…”
Section: Introductionmentioning
confidence: 99%